The Sustained and Selective Effectiveness of a Videophone Conversation for Individuals with Dementia - Yasuda, Kiyoshi; Narumoto, Jin; Sano, Mutsuo; Kuwahara, Noriaki; Kuwabara, Kazuhiro (Journal of Alzheimer's Research and Therapy, 2019)
Studies reported that a videophone conversation allows individuals with dementia to be psychologically stable even after a 3 h conversation session. The individuals who exhibited difficulty in watching TV programs could still enjoy a conversation. This follow-up study investigated the effectiveness of a videophone conversation using five subjects with mild to moderate dementia. Two sessions were conducted during the study. In Session A, a subject convers with a talking partner through videophone for 30 min, and in Session B, a subject watches his/her favorite TV program. Sessions A and B were rotated on a day-by-day basis. Their psychological stability was evaluated by caregivers using the revised GBS scale (concomitant evaluation) and the overall psychological stability 3 h after each session (delayed evaluation) was also assessed. The significant psychological stability was obtained for two subjects in the concomitant evaluation, and one subject in the delayed evaluation. This indicates that a videophone conversation is a promising remote intervention for assisting individuals with dementia. Further investigation with the participation of more subjects must be conducted.
Keywords: Videophone; Remote; Dementia; Conversation; Skype™